2014
DOI: 10.1007/s10995-014-1646-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Institutional Delivery Among Women of Childbearing Age in Rural Haiti

Abstract: Institutional delivery is an important factor associated with reduced maternal mortality rate (MMR). MMR in Haiti is high (350 per 100,000) and institutional delivery is low-just over 25 % of women delivered at a health facility in 2010. There also exists substantial rural-urban disparity in delivery with more hospital deliveries in urban than in rural areas. We aimed to study the prevalence and determinants of institutional delivery in a sample of women of childbearing age in rural Haiti. The study took place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
5
14
1
Order By: Relevance
“…A few studies have looked at social contextual factors such as community norms, media access, and the level of local development 12 15 . In Haiti, a few studies have found that facility delivery was associated with maternal and birth characteristics, household poverty, use of antenatal care services, and community exposure to mass media 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…A few studies have looked at social contextual factors such as community norms, media access, and the level of local development 12 15 . In Haiti, a few studies have found that facility delivery was associated with maternal and birth characteristics, household poverty, use of antenatal care services, and community exposure to mass media 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…We analyzed data from a cross-sectional household based survey conducted from October to November 2011 in a predominantly rural region of about 65,000 inhabitants situated in the southern region of Haiti. The survey design and procedures have been described previously [ 23 , 24 ]. Briefly, a total of 800 households were selected for the survey using a two-stage sampling methodology.…”
Section: Methodsmentioning
confidence: 99%
“…In 2010, institutional deliveries were just over 25% of all Haitian births. A cross-sectional study conducted by Seraphin et al (2015) at Fond des Blancs and Villa, a rural and isolated region of about 65,000 inhabitants, aimed to identify factors contributing to women's access to medical care during obstetrical emergencies. Study participants were women of childbearing age (15-49) who gave birth in the five years preceding the survey (N = 575), (Seraphin.…”
Section: Healthcare Facility Deliveries In Rural Haitimentioning
confidence: 99%
“…In order to implement interventions to decrease MMR in low and middle-income countries, factors of preventive delivery care seeking behaviors need to be understood. Seraphin et al, (2015) state that in low income countries like Haiti, antenatal care provided by nongovernmental organization (NGO) offers an educational opportunity to motivate women to choose institutional delivery and thereby reduce maternal and infant mortality:…”
Section: Healthcare Facility Deliveries In Rural Haitimentioning
confidence: 99%
See 1 more Smart Citation